Wave transmission from asymmetrical changes of cross-sectional area in a beam - Takiuti, B. E. [UNESP]; Manconi, E.; Brennan, M. J. [UNESP]; Junior, V Lopes [UNESP] (IOP Publishing, 2019)
In this paper wave scattering from an asymmetrical change of cross-sectional area in a beam is numerically studied. Incident symmetric and antisymmetric Lamb waves are considered and multiple wave mode conversion due to interaction with the discontinuity are investigated up to high frequency (above the cut-off of the second symmetric Lamb wave mode, S 2). Results are presented in terms of transmission power coefficients, kinetic energy, and energy velocity. These are evaluated using the Wave Finite Element method to predict the wave modes from FE cross-sectional nodal displacements and nodal forces. It is shown that the methodology proposed can give an insight into wave scattering and multiple converted Lamb wave modes, which can be useful in Structural Health Monitoring.
Keywords: damage detection; finite element; structural health monitoring; wave scattering